144k views
4 votes
Solve 7+3(2g-6)= -29

2 Answers

4 votes

Answer:

g = -3

Explanation:


7+3(2g-6)= -29\\\\\mathrm{Subtract\:}7\mathrm{\:from\:both\:sides}\\\\7+3\left(2g-6\right)-7=-29-7\\\\Simplify\\\\3\left(2g-6\right)=-36\\\\\mathrm{Divide\:both\:sides\:by\:}3\\\\(3\left(2g-6\right))/(3)=(-36)/(3)\\\\Simplify\\\\2g-6=-12\\\\\mathrm{Add\:}6\mathrm{\:to\:both\:sides}\\\\2g-6+6=-12+6\\\\Simplify\\\\2g =-6\\\\\mathrm{Divide\:both\:sides\:by\:}2\\\\(2g)/(2)=(-6)/(2)\\\\Simplify\\\\g =-3

User Beaslera
by
5.7k points
7 votes

Answer:

g=-3

Explanation:

7+3(2g-6)=-29

7+6g-18=-29

6g=-29+18-7

6g=-18

g=-3

I think this is the right answer :D hope this helps ;)

User Dyllon
by
5.2k points